European integration trends in the development of the state employment policy of youth in Ukraine - Minenko , Volodymyr; Zhadan , Oleksandr (Theory and Practice of Public Administration, 2019)
The article is devoted to the definition of the main tendencies of the development of the state youth employment policy in Ukraine in the conditions of European integration. The current state of employment and unemployment of youth in Ukraine and in the world is analyzed. The most actual problems in the field of realization of labor activity of youth on the national labor market are revealed, among them: high unemployment among young people; mismatch of the acquired professional knowledge and skills to the needs of the labor market; problems with the employment and career development of people with disabilities, gender barriers in the labor market; high youth employment in the informal economy, especially in rural areas; the growth of the youth labor migration rate. It is determined that the development of European integration processes in Ukraine in the field of formation and implementation of the state youth employment policy takes place within the framework of systematic implementation of EU legislation in the field of social and labor relations in the national labor market. That is, a complex of interrelated measures aimed at improving the forecasting of needs in specialists of different professional qualification levels is realized; systems of education, training and retraining of specialists, state stimulation of cooperation between institutions of higher education with science and production; social insurance system; systems of national, regional and local employment services. Specific programs for vocational training, employment, funds are allocated specifically for young people, the links between educational institutions and industry are strengthened, laws are adopted, other measures aimed at reducing the gap, in comparison with other groups of the population, in the employment opportunities of young people. The Association Agreement calls on Ukraine to ratify the ILO conventions and bring the legislation closer to the EU directives. Ukraine has already ratified all major ILO conventions. In general, the implementation of the Association Agreement will help to bring Ukrainian regulation in the field of labor to the best international practice. At the same time, attention should be focused not only on legislative work, but also on measures that will ensure the implementation of the legislation on youth employment.